Design and implementation of grid tied high step-up DC-DC converter with switched capacitor - Sethi, Binapani; Mitra, Lopamudra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
In this paper, the design and implementation of a three-phase grid-connected inverter coupled with a high step-up DC-DC converter with a switched capacitor is demonstrated. In this converter two capacitors are utilized with a coupled inductor. The charging of capacitors takes place parallel and discharging in series during switch off and switch on time respectively. The energization of the coupled inductor provides the high voltage gain. The passive clamp circuit is used to recycle the leakage energy of the inductor circuit. Therefore, the switch stress is reduced. This high gain converter is given DC input of 40 V and a high voltage 538 V obtained is supplied to the grid connected inverter which uses sinusoidal pulse width modulation (SPWM), to obtain 3phase line-neutral voltage of 415 V from inverter for grid synchronization. A high voltage gain of 13 and efficiency of 96% is obtained for different load and voltage variation. The modeling and the simulation are done using physical security information management (PSIM) software and all the results are presented in this paper.